Emerging Mechanisms and Targeted Therapy of Pyroptosis in Central Nervous System Trauma - Yang, Biao; Zhong, Weijie; Gu, Ying; Li, Yi (Frontiers in Cell and Developmental Biology, 2022)
It has been confirmed that iron death, pyroptosis, apoptosis, and necroptosis are different death modes of cells. Recent studies have shown that pyroptosis can be effectively regulated. Like necroptosis, pyroptosis has been regarded as a type of programmed cell death. The mechanism of its occurrence could be divided into canonical inflammasome-induced pyroptosis and non-canonical inflammasome-induced pyroptosis. In the past research, pyroptosis has been shown to be closely related to the event of various diseases, such as tumors, neurodegenerative diseases, and central nervous system trauma, etc. Studies have pointed out that in central nervous system trauma, pyroptosis was activated, and by inhibiting the occurrence of pyroptosis, it can play a role in protecting nerve function. In this review, we summarized the mechanism of the event and development of pyroptosis, introduced the treatment strategies of targeted pyroptosis in central nervous system trauma, and proposed some issues of targeted pyroptosis in the treatment of central significant nervous system injury.